SURG-07. The impact of early targeted therapy on the neurosurgical approach to pediatric low-grade glioma. (3rd June 2022) - Piatelli, Gianluca; Pavanello, Marco; Piccolo, Gianluca; Rossi, Andrea; Garrè, Maria Luisa; De Marco, Patrizia; Iurilli, Valentina; Antonelli, Manila; Gaggero, Gabriele; Caruggi, Samuele; Verrico, Antonio; Crocco, Marco; et al.
Abstract: We report two cases of pediatric low-grade glioma (pLGG) treated with vemurafenib, an oral BRAF -inhibitor: a 12-year-old girl with involvement of basal ganglia, hypothalamus, and diencephalic junction; a 3-year-old boy, with an optic pathway/hypothalamic glioma extending along the left optic tract and basal ganglia. Both received a biopsy and molecular analysis was performed in the girl's tumor, showing BRAF V600E mutation. Therefore, instead of surgical removal planned by neurosurgeons, first-line treatment with vemurafenib was started: after one month 45% reduction of the mass according to RANO criteria was found, as well as better balance control and strong reduction of the right arm paresis; five months later, a 70% shrinkage was detected, stabilized to 76% after a year. The young boy first started chemotherapy with vincristine and carboplatin, but at the end of the induction phase the tumor had increased and ascites, hydrocephalus, and visual impairment occurred. Molecular testing showing BRAF V600E mutation on the initial tumor biopsy was obtained; therefore, the surgical option was postponed and therapy with vemurafenib started. After only three days, visual acuity and muscle tone improved; brain MRI showed a 34% reduction of the mass after one week, increased up to 65% after six months. Therefore, no ulterior surgery was necessary. In pLGG, the neurosurgical biopsy is essential to let an early and rapid molecular diagnosis of BRAF mutations and guide subsequent targeted therapies. Our cases demonstrate how a prompt radiological response to vemurafenib and the related clinical improvement can influence both therapeutic and surgical decisions, hopefully reducing the occurrence of second neurosurgery with associated risks of neurological sequelae. To our knowledge, this is the first report assessing such a quick shrinkage in pLGG treated with vemurafenib, highlighting the importance of an early investigation of BRAF status in all cases of LGG in children.